Nominating an addressee in modern religious epistles - Тарасюк, Тетяна (Київський національний університет імені Тараса Шевченка, 2018)
The religious communication process involves two communicants, namely a priest (the author) and a potential believer (addressee). The nominative field of the addressee in the religious style requires more detailed scientific studies. The purpose of the article is to analyze the peculiarities of the addressee’s nomination in modern religious epistles of the highest-rank clergy of the Ukrainian churches. The recipient (addressee) of the texts under study is determined not only by the church status (the priest – the monk – the believer), but also by the confessional, eparchian, partly by territorial and professional affiliation and by the subject matter of the epistles themselves. It has been revealed that all the lexemes under study fall into two major categories: nominatives (names) and appellatives (appeals) according to language functional spheres, namely the sphere of representation and sphere of appeal. The authors of the religious epistles use nominatives predominantly in the epistle titles to name the addressees, whom they are appealing to, while appellatives are used in the introductory greetings, at the beginning of the epistle, and are aimed at enhancing the attention of the recipients throughout the text. The addressee’s names are represented by three lexical-semantic groups: “clergy”, “monks”, “believers” with the core lexemes typical of religious discourse. Such lexemes, except for sporadic one-component use, are most often intensified by stylistically marked qualifying attributes. In terms of the structure of emotionally-evaluative expressions, epithet-based nominations dominate, among which we distinguish functionally-marked lexemes (Worthy/Respectable, Reverend, Most Reverend, Godloving, etc.) and commonly used lexemes, mainly adjectives of intimate semantics (Dear, Beloved, Loving) including official-ceremonial – Dear, Honourable. Optional lexico-grammatical structure of appeals is represented by various-style lexemes, which are not typical of the religious style. For example, typical for conversational style appelative lexemes appear to be combined with functionally differentiated attributes of religious semantics. Thus, the lexeme of general use children is often combined with epithets spiritual, church; stylistically marked lexical units pastors, brothers and sisters, conventional for official, business or colloquial styles, are used with the attributes dear, honourable, close to my heart.

Проаналізовано найменування адресата в сучасних релігійних посланнях вищого духовенства українських церков. Простежено вплив тематики та функційної ролі таких найменувань на лексичний склад досліджуваних конструкцій. Встановлено типові для релігійного спілкування номінативи й апелятиви, а також кваліфікативні означення до них. З’ясовано, що номінативами автори послань послуговуються для звертання до адресата, апелятивами – для вступних привітань на початку текстів та для активізації уваги реципієнта протягом усього тексту.
Найменування адресата в сучасних релігійних посланнях
Keywords: адресат; номінативи; апелятиви; релігійне послання; релігійна комунікація; addressee; nominatives; appellatives; religious epistle; religious communication